A Distribution Free Interval Estimate for Coefficient Alpha. Issue 6 (2nd November 2018) - Trinchera, Laura; Marie, Nicolas; Marcoulides, George A.
Abstract : Scales are important tools for obtaining quantitative measures of theoretical constructs. Once a set of measures to be used in a scale is selected, reliability is commonly examined in order to assess their measurement quality. To date, Cronbach's coefficient alpha is the most commonly reported index of measurement quality for assessing scale reliability. In this paper, an asymptotic distribution of the natural estimator of coefficient alpha is derived. A new interval estimate and a statistical test on the significance of the sample estimate of the coefficient are also presented. The proposed approach is compared to four popular methods commonly used to compute confidence intervals (CI) for alpha using a Monte Carlo simulation study. An R function for implementing the proposed CI approach is also provided.